Indoor air bacterial load and antibiotic susceptibility pattern of isolates at Adare General Hospital in Hawassa, Ethiopia - Atalay, Yibeltal Assefa; Mengistie, Embialle; Tolcha, Alemu; Birhan, Belete; Asmare, Getachew; Gebeyehu, Natnael Atnafu; Gelaw, Kelemu Abebe (Frontiers in Public Health, 2023)
Background: Air is the agent of pathogenic microbes which cause significant problems in the hospital environment. The Multidrug resistance which could pose a major therapeutic challenge to these airborne microorganisms in hospital indoor environments. Method and materials: This study was conducted at Adare General Hospital in Hawassa City, Sidama, Ethiopia. A cross-sectional study was conducted. The proportional allocation method was used to select the sampled 50 rooms from the total available rooms in each category of wards and staff offices. A total of 100 indoor air samples were collected using settle plates in all units twice a day, mornings (9:00 am - 4:00 am) and afternoons (3:00 pm - 4:00 pm). The types and number of colonies were determined in the laboratory and the Pathogenic bacteria were isolated by appropriate bacteriological techniques. The antimicrobial susceptibility testing was done on Mueller-Hinton agar for every potential pathogenic bacteria isolated with 12 antibiotics each by Kirby-Bauer disk diffusion method matching the test organism to 0.5 McFarland turbidity standards. Data was entered and analyzed using the SPSS version 25 window. Descriptive analysis and One-way analysis of variance were performed. Results: The indoor air bacterial load of Adare General Hospital was found in the range between 210 & 3224 CFU/m3. The highest indoor air bacterial load was identified from the Gynecology ward with a mean of 2542.5CFU/m3 at (p<0.05). From 100 indoor air samples, a total of 116 bacterial pathogen isolates were attained. Gram-positive isolates predominated at 72.4% of which 37.1% were Staphylococcus aureus, 26.7% were Coagulase-negative staphylococci, and the rest 8.6% were Streptococcus pyogenes. The isolation of pathogenic bacteria Staphylococcus aureus and Coagulase-negative staphylococci showed a high level of resistance to Ampicillin. Conclusions: A high bacterial load was found in the study area as compared to different indoor air biological standards. Staphylococcus aureus and Coagulase-negative staphylococci were the isolated predominant bacteria. Attention should be given to preventing and minimizing those environmental factors that favor to multiplication of bacteria in the indoor environment of a hospital to safe health of patients, visitors, and staff. Keywords: Bacteria load, Bacterial isolate, Drug resistance, Indoor air quality, Ethiopia